Fostering Innovative Organisations for Sustainability : a case study on a Swedish packaging and paper material company - Brown, Melanie; Ekman, Lisa (SLU/Dept. of Economics, 2022)
The Swedish pulp and paper industry is affected by increased sustainable development pressures such as climate impact and resource efficiency, which makes sustainability a strategic priority in this sector. At the level of individual firms, implementing a corporate sustainability strategy must involve all parts of the organisation. In such instances, management plays an important role to practically link all parts of the organisation with the development of more sustainable ways of conducting business. Indeed, developing new ways of conducting business must involve the creation of innovative organisations (IO); that is a business organised to produce innovative outcomes. However, a key management challenge when creating IO for sustainability is to engage employees in all parts of the organisation. Therefore, the aim of this study is to contribute to the understanding of management practices of engaging employees in fostering more IO for sustainability. To address the aim, previous literature on IO, management practices and employee engagement are combined with empirical data from a case study firm. Qualitative research methods were used, such as semi-structured interviews, focus groups and questionnaires. The empirical result shows that the firm deploys several different management practices to foster a more IO. The study also shows that employees' perceptions and engagement regarding these practices can vary depending on the individual and in what way the management practice is performed. However, this study identifies that the fostering of IO for sustainability is widely dependent on its context and relies on the dynamic structure between employees and managers. Nevertheless, this study makes an important contribution to the area of corporate sustainability management literature. Specifically, it makes an analytical link between corporate strategy making and the role of managers in fostering IO for sustainability. By conceptualising management practices as context dependent and as a dynamic interplay between managers and employees, the study offers a better way of understanding the links between management practices and employee engagement in fostering IO for sustainability. While the insights from the case study are context dependent, the conceptual framework and methods deployed in this study for investigating management practices can be implemented by others, such as researchers, consultants or managers for the purpose of fostering more IO for sustainability in other contexts and further exploring the dynamics between people at all levels of the firm. Therefore, as this study shows the importance of investigating management practice in the setting where it occurs, future studies are needed to examine the management practices in other industry contexts and further explore the dynamic interplay between all levels of the firm.